Mutation of A677 in histone methyltransferase EZH2 in human B-cell lymphoma promotes hypertrimethylation of histone H3 on lysine 27 (H3K27) - McCabe, Michael T; Graves, Alan P; Ganji, Gopinath; Diaz, Elsie; Halsey, Wendy S; Jiang, Yong; Smitheman, Kimberly N; Ott, Heidi M; Pappalardi, Melissa B; Allen, Kimberly E; Chen, Stephanie B; Della Pietra, Anthony III; et al. (Proceedings of the National Academy of Sciences - PNAS, 2012)
Trimethylation of histone H3 on lysine 27 (H3K27me3) is a repressive posttranslational modification mediated by the histone methyltransferase EZH2. EZH2 is a component of the polycomb repressive complex 2 and is overexpressed in many cancers. In B-cell lymphomas, its substrate preference is frequently altered through somatic mutation of the EZH2 Y641 residue. Herein, we identify mutation of EZH2 A677 to a glycine (A677G) among lymphoma cell lines and primary tumor specimens. Similar to Y641 mutant cell lines, an A677G mutant cell line revealed aberrantly elevated H3K27me3 and decreased monomethylated H3K27 (H3K27me1) and dimethylated H3K27 (H3K27me2). A677G EZH2 possessed catalytic activity with a substrate specificity that was distinct from those of both WT EZH2 and Y641 mutants. Whereas WT EZH2 displayed a preference for substrates with less methylation [unmethylated H3K27 (H3K27me0):me1:me2 kcat/Km ratio = 9:6:1] and Y641 mutants preferred substrates with greater methylation (H3K27me0:me1:me2 kcat/Km ratio = 1:2:13), the A677G EZH2 demonstrated nearly equal efficiency for all three substrates (H3K27me0:me1:me2 kcat/Km ratio = 1.1:0.6:1). When transiently expressed in cells, A677G EZH2, but not WT EZH2, increased global H3K27me3 and decreased H3K27me2. Structural modeling of WT and mutant EZH2 suggested that the A677G mutation acquires the ability to methylate H3K27me2 through enlargement of the lysine tunnel while preserving activity with H3K27me0/me1 substrates through retention of the Y641 residue that is crucial for orientation of these smaller substrates. This mutation highlights the interplay between Y641 and A677 residues in the substrate specificity of EZH2 and identifies another lymphoma patient population that harbors an activating mutation of EZH2.